Patterns of variability in supercritical hadronic systems - Petropoulou, M.; Mastichiadis, A. (OUP, 2018)
A unique and often overlooked property of a source loaded with relativistic protons is that it can become supercritical, i.e. it can undergo an abrupt transition from a radiatively inefficient to a radiatively efficient state once its proton energy density exceeds a certain threshold. In this paper, we investigate the temporal variability of hadronic systems in this hardly explored regime. We show that there exists a range of proton densities that prevent the system from reaching a steady state, but drive it instead in a quasi-periodic mode. The escaping radiation then exhibits limit cycles, even if all physical parameters are held constant in time. We extend our analysis to cases where the proton injection rate varies with time and explore the variability patterns of escaping radiation as the system moves in and out from the supercritical regime. We examine the relevance of our results to the variability of the prompt gamma-ray burst emission and show that, at least on a phenomenological level, some interesting analogies exist.
Keywords: astroparticle physics; Astrophysics - High Energy Astrophysical Phenomena; gamma-ray burst: general; INSTABILITIES; radiation mechanisms: non-thermal